Механизм управления организационным поведением сотрудников предприятий - Дорофеева, А.А. (Стратегія і механізми регулювання промислового розвитку, 2014)
Разработана каузальная модель формирования организационного поведения сотрудника, которая позволяет идентифицировать основные причинно-следственные факторы, оказывающие влияние на формирование устойчивой модели поведения сотрудников и формы ее реализации в организационной системе. Предложен состав мотивационного механизма управления организационным поведением персонала, состоящего из двух частей: мотивационного механизма формирования моделей организационного поведения и организационного механизма управления поведенческими интенциями. Механизм позволит формировать на предприятиях устойчивые позитивные поведенческие модели персонала. Розроблено каузальну модель формування організаційної поведінки співробітників, яка дозволяє ідентифікувати основні причинно-наслідкові фактори, що впливають на формування стійкої моделі поведінки співробітників і форми її реалізації в організаційній системі. Запропоновано склад мотиваційного механізму управління організаційною поведінкою персоналу, що складається з двох частин: мотиваційного механізму формування моделей організаційної поведінки та організаційного механізму управління поведінковими інтенціями. Механізм дозволить формувати на підприємствах стійкі позитивні поведінкові моделі персоналу. Key factors that determine the organizational behavior of staff were studied, important steps in the management of organizational behavior were identified: formation of the external motivation, formation of behavior patterns and determining the form of staff behavior model implementation. A causal model of employee organizational behavior formation was developed that allows identifying the main causal factors that influence the formation of a stable model of employee behavior and forms of its implementation in the organizational system. A structure of mechanism of managing organizational behavior of enterprise staff was proposed, consisting of two parts: the motivational mechanism of organizational behavior model formation and organizational mechanism of behavioral intention management. The mechanism of organizational behavior model formation will allow enterprises to form a stable positive behavior of staff. The organizational mechanism of behavioral intention management, that includes organizational and administrative tools for adjusting the forms of implementing staff behavior models is a promising direction of research that is necessary for the practical implementation of enterprise management system of the motivational mechanism of organizational behavior management that is currently being developed. It’s proposed to assess the effectiveness of the proposed Mechanism of managing organizational behavior of enterprise staff using two criteria: in terms of improving the quality of work, increasing productivity, and in terms of the quality of labor resources: reducing turnover, retirement, staff training and replacement costs. Since organizational behavior management methods that are proposed in the concept and in the corresponding mechanism are low costs, it is safe to assume that their implementation in enterprises will increase the efficiency of labor resources, as well as the efficiency of the production and administrative activities of enterprises staff.